Fabrication and characterization of agarwood extract-loaded nanocapsules and evaluation of their toxicity and anti-inflammatory activity on RAW 264.7 cells and in zebrafish embryos - A. Eissa, Manar; Hashim, Yumi Zuhanis Has-Yun; Mohd Nasir, Mohd Hamzah; Ahmad Nor, Yusilawati; Mohd Salleh, Hamzah; Md Isa, Muhammad Lokman; Syed Abd Azizz, Saripah Salbiah; Abd Warif, Nor Malia; Ramadan, Eman; M. Badawi, Noha (Taylor & Francis, 2021)
Aquilaria malaccensis has been traditionally used to treat several medical disorders including inflammation. However, the traditional claims of this plant as an anti-inflammatory agent has not been substantially evaluated using modern scientific techniques. The main objective of this study was to evaluate the anti-inflammatory effect of Aquilaria malacensis leaf extract (ALEX-M) and potentiate its activity through nano-encapsulation. The extract-loaded nanocapsules were fabricated using water-in-oil-in-water (w/o/w) emulsion method and characterized via multiple techniques including DLS, TEM, FTIR, and TGA. The toxicity and the anti-inflammatory activity of ALEX-M and the extract-loaded nanocapsules (ALEX-M-PNCs) were evaluated in-vitro on RAW 264.7 macrophages and in-vivo on zebrafish embryos. The nanocapsules demonstrated spherical shape with mean particle diameter of 167.13 ± 1.24 nm, narrow size distribution (PDI ¼ 0.29 ± 0.01), and high encapsulation efficiency (87.36 ± 1.81%). ALEX-M demonstrated high viability at high concentrations in RAW 264.7 cells and zebrafish embryos, however, ALEX-M-PNCs showed relatively higher cytotoxicity. Both free and nano encapsulated extract expressed anti-inflammatory effects through significant reduction of the pro-inflammatory mediator nitric oxide (NO) production in LPS/IFNc-stimulated RAW 264.7 macrophages and zebrafish embryos in a concentration-dependent manner. The findings highlight that ALEX-M can be recognized as a potential anti-inflammatory agent, and its anti-inflammatory activity can be potentiated by nano-encapsulation. Further studies are warranted toward investigation of the mechanistic and immunomodulatory roles of ALEX-M